Tracing Accounting in Javanese Tradition - Ari Kamayanti; Nurmala Ahmar (Yayasan Rumah Peneleh, 2019)
This paper aims to trace the perseverance of accounting in slametan as one of Javanese tradition. Through reading of old scriptures dated as far as 1030AC as well as observing the existing phenomena of slametan, underlying values of slametan are explored and reconciled. It is found that the survival of accounting in the Javanese tradition not only exists in the form of physical recordings but also mental recordings. Cohesiveness /togetherness among the people, and spiritual as well as religious beliefs give rise to social obligations, mental recordings, and soul-spiritual gain.